1974
DOI: 10.1159/000180257
|View full text |Cite
|
Sign up to set email alerts
|

Use of Metolazone, a New Diuretic, in Patients with Renal Disease

Abstract: Metolazone, a new diuretic/saluretic/anti-hypertensive agent related to quinethazone, was used to treat 20 patients with impaired renal function. Among eight water loaded hospitalized patients given metolazone 5 mg intra venously, glomerular filtration rate rose in four and diminished slightly in four while urine flow and sodium excretion in creased significantly. In 12 out-patients given long-term oral metolazone (usually 5–10 mg in single daily doses) treatment effectively removed oedema and induced weight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…As detailed in Table 1, these early studies included 5 small heterogeneous trials of metolazone in CKD all with a before-and-after design [22][23][24][25][26], and in general GFR was low with 2 trials reporting creatinine clearances for individual subjects as low as 1 mL/min. These studies showed an improvement in reported diuretic or antihypertensive outcomes with metolazone administration, and these early positive results are likely the reason that there is a persistent belief that metolazone is the unique thiazide that is effective in advanced CKD [27].…”
Section: Older Studies Of Thiazides In Ckdmentioning
confidence: 99%
“…As detailed in Table 1, these early studies included 5 small heterogeneous trials of metolazone in CKD all with a before-and-after design [22][23][24][25][26], and in general GFR was low with 2 trials reporting creatinine clearances for individual subjects as low as 1 mL/min. These studies showed an improvement in reported diuretic or antihypertensive outcomes with metolazone administration, and these early positive results are likely the reason that there is a persistent belief that metolazone is the unique thiazide that is effective in advanced CKD [27].…”
Section: Older Studies Of Thiazides In Ckdmentioning
confidence: 99%
“…The dose in patients with severe renal insufficiency should probably not exceed 20 mg/day (Table 5) (DARGIE et al 1972;CRASWELL et al 1973;PATON and KANE 1977). Secondary action ot related to carbonic anhydrase inhibitory activity, but due to interference with Na phosphate cotransport Primary action related to an ability to interfere with activity of the need be given only once daily or every other day.…”
Section: Commentsmentioning
confidence: 99%
“…Alternatively, metolazone administered with a loop diuretic can be uniquely successful in effecting a diuresis in edematous or diuretic‐resistant patients. Furosemide has been the loop diuretic most commonly administered with metolazone in clinical practice 1–25 . The basis for combination diuretic therapy is the principle of sequential nephron blockade: i.e., the proximal and more primary distal site of action of metolazone bolstering the effect of furosemide within the loop of Henle 26 .…”
mentioning
confidence: 99%
“…Chronic renal failure. Metolazone monotherapy has occasionally proved effective in eliciting a diuretic response in advanced renal failure, 9,45–47 which has not always been the case with other thiazide diuretics 48 . A diuretic response has been demonstrable in the presence of an extremely low glomerular filtration rate (GFR), 1,5,7,9,19,27 as well as in patients undergoing maintenance hemodialysis 25,28,47 .…”
mentioning
confidence: 99%
See 1 more Smart Citation